European telecommunications policy research: proceedings... - Garnham, N. ed (IOS AmsterdamNL, 1989)
Deals with issues relevant to European and international telecommunications policy makers such as current regulatory developments; problems arising from the introduction of Integrated Services Digital Networks (ISDN); user perspectives on new telecommunications networks and the economics of networks.